PENGARUH KINERJA ENVIRONMENTAL, SOCIAL, AND GOVERNANCE (ESG) TERHADAP KINERJA KEUANGAN PERUSAHAAN DENGAN KEKUATAN CHIEF EXECUTIVE OFFICER (CEO) SEBAGAI VARIABEL MODERASI DI BURSA EFEK INDONESIA - Simanjuntak, Howard; Yuliusman, Yuliusman; Safelia, Nela (Jambi Accounting Review (JAR), 2025)
This study aims to analyze the influence of environmental, social, and governance (ESG) performance on corporate financial performance, with CEO characteristics as a moderating variable on the Indonesian Stock Exchange. The sample used in this study were companies listed on the Indonesia Stock Exchange in 2020-2022 that had ESG distribution scores in the Revinitif Eikon database. Using a purposive sampling method, a sample of 17 companies was obtained. This study employed moderated regression analysis (MRA) tested using Eviews12. The results showed that environmental and social performance did not significantly influence corporate financial performance, while corporate governance performance did significantly influence corporate financial performance. Meanwhile, the CEO power variable was unable to moderate (strengthen) the relationship between environmental, social, and governance performance and corporate financial performance.